Design of a Split Ring Resonator Integrated with On‐Chip Terahertz Waveguides for Colon Cancer Detection. Issue 9 (1st July 2022) - Park, Sae June; Tucker, Robyn; Pickwell‐MacPherson, Emma; Cunningham, John E.
Abstract: Finite element method (FEM) simulations (employing ANSYS High Frequency Structure Simulator, HFSS) are used to investigate the response of terahertz (THz) frequency range split‐ring resonators (SRRs) integrated with on‐chip THz waveguides to cancerous tissues. Two‐port S‐parameter simulations are performed to obtain the transmission spectra (S21 ) of a planar Goubau line (PGL) integrated with an SRR. Permittivity and loss tangent of the colonic tissues are both taken into account in the numerical simulation. The transmission spectra of the SRR integrated PGL are obtained for cancerous and healthy tissues in close proximity to the SRR, and it is found that they can be distinguished by the resonant frequency shift of the SRR induced by dielectric loading. The electric field distribution and magnitude near the SRR for various capacitive gap widths of SRR are investigated to understand how the gap width affects the maximum electric field magnitude and the vertical extent of the electric field in the gap area. The simulated imaging of colonic tissue consisting of healthy and cancerous tissues using the SRR integrated PGL device with a protective layer on it is performed, showing how the technique could in principle be used to distinguish tumor margins with realistic THz dielectric parameters. Abstract : This work presents a novel approach for detecting colorectal cancer tissue in the colon by integrating split‐ring resonator into on‐chip terahertz waveguides. It is shown that the split‐ring resonator integrated Goubau line can be used to image colorectal tissue and distinguish cancerous colonic tissue from healthy colonic tissue.